Propriedades estruturais e vibracionais da monoetalonamina com o metal de transição Cu2+ - Branco, Jonathan Schavetock (2024)
In the framework of this work, the structural and vibrational properties of monoetalo namine (MEA) were investigated in complexes with the transition metal Cu2+. The choice of this ligand and these metals derives from the interest in developing new compounds that can help in the nutrition, protection, and growth of agricultural crops. For this purpose, experimental studies of X Ray difraction (XRD), infrared spectroscopy were conducted by Fourier Transformation (FT-IR) and Raman, both at ambient temperature and pressure, and Thermogravimetric Analysis (TG-DTA) in the Spectroscope Laboratories of the Federal University of Mato Grosso (UFMT). Additionally, molecular structures were created, modeled, and optimized using various software, and computational calculations were carried out to obtain vibrational frequencies, using the Potential Energy Distribution (PED) and the Functional Density Theory (DFT) with the functional B3LYP and the 6-311++g(d,p) and cc-pVDZ base sets. The analysis of these results allowed the accurate assignment of the molecular vibrations present in the Raman and Infrared spectra of the samples, characterizing two new organic compounds with potential to be explored by the agrochemical industry.